Motivasi Ibu Bekerja Dengan Tahap Perkembangan Keluarga Anak Usia Remaja Di Kota Tangerang - Rina Puspitasari (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
Background: Working mother has a role as a worker and a mother including caring for children. Working mother which is caring adolescent are classified as middle adulthood, having the characteristics of career advancement and are responsible for health changes. Objective : This study aimed to gain an overview of working mothers’s motivation to take care adolescence. Methods : This study used qualitative research methods with a phenomenological approach. A purposive sample of eight participants were involved in the study. Data were collected through in depth interviews. Data analysis used the Collaizzi's method. Result : The results of the study of working mother’s motivation includes meeting the needs of self-actualization, meeting the economic needs of the family and meeting psychological needs. This result can be used by occupational health nursing to provide nursing intervention.Conclusion : Motivation of mothers to work with the stages of family development of adolescents to meet the needs of self-actualization including sustainable ideals, expanding relationships, and self-development; meet the economic needs of the family. Keywords: working mothers, adolescence, motivation